PENGARUH DEWAN KOMISARIS, KOMISARIS INDEPENDEN, DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN PERUSAHAAN DI MASA PANDEMI COVID – 19 - Via Ayu Pratiwi; Yefta Andi Kus Noegroho (TEMA, 2022)
The research aims to examine the effect of the variables of the board of commissioners, independent commissioners and managerial ownership on financial performance as measured by Return on Assets (ROA) during the covid-19 pandemic. Board of commissioners and independent commissioners have a role to mo-nitor and provide input for managers to support processes within the company. Ma-nagerial ownership is share ownership owned by managerial parties so that they can take part in decision making and encourage activities within the company. This study was tested by testing the classification assumption and multiple regression with samples and populations of 31 major energy companies listed on the Indonesia Stock Exchange (IDX) and publishing their annual report for the period 2018 – 2020. The results show that: (1) the board of commissioners has a positive effect and significant effect on financial performance, (2) independent commissioners have a negative and insignificant effect on financial performance, (3) managerial ownership has a positive and significant effect on financial performance.